Franco Vaccari. Experiencing darkness towards Shamanism - Sergio Poggianella (Agathón)
This paper examines one of the most symbolic and meaningful artworks by Franco Vaccari, Dark Sculpture, an artwork/temporary performance in which darkness becomes a play of presence-absence, inspired, both conceptually and visually, by the transition from light to dark. A labyrinthine darkness that enhances the other senses and helps to rediscover the light forms of the Spirit worlds that are concealed precisely by the optical space, so they can’t be seen. The Shaman passes through these dream states and Spirit worlds – in an altered state of consciousness – in order to recover the souls of the humans closest to him, lost after an illness. Dark spaces in which, as Vaccari states, the forms that may be encountered become unexpected events with hallucinating features.